1972
DOI: 10.1520/jfs10142j
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chemical Determinations on Vitreous Humor in Forensic Pathology

Abstract: It is frequently important in deciding the cause of death to be able to determine chemical abnormalities which may have existed prior to demise. This is particularly true in cases where clinical history suggests the possibility of such chemical abnormalities, but opportunity for autopsy does not exist. Even when a postmortem examination is done, determination of chemical abnormalities may help establish the cause of death where the autospy findings are inconclusive or may validate the significance of recogniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 7 publications
0
44
1
Order By: Relevance
“…This results in further mobilisation of liver glycogen and release of glucose into the blood circulation as a counterbalancing phenomenon [18]. Due to the difficulty interpreting postmortem blood glucose levels, other fluids have been proposed as being more reliable in the estimation of antemortem blood glucose concentrations, particularly the cerebrospinal fluid and vitreous humor [19][20][21][22][23][24]. Investigation of the biochemical constituents of the vitreous humor have been periodically performed by several authors [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in further mobilisation of liver glycogen and release of glucose into the blood circulation as a counterbalancing phenomenon [18]. Due to the difficulty interpreting postmortem blood glucose levels, other fluids have been proposed as being more reliable in the estimation of antemortem blood glucose concentrations, particularly the cerebrospinal fluid and vitreous humor [19][20][21][22][23][24]. Investigation of the biochemical constituents of the vitreous humor have been periodically performed by several authors [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the postmortem identification of hypoand hyperglycaemia still remains interesting subjects of research. Coe [20,21,23,28] demonstrated that there was a consistent but variable decrease in vitreous glucose concentrations with increasing postmortem time in non-diabetic individuals, whereas postmortem glycolysis had little effect on the elevated vitreous glucose values of uncontrolled diabetics. Given the assumption that glucose is converted into lactate after death and to eliminate the negative effect of postmortem glycolysis, Traub proposed that antemortem blood glucose concentration could be estimated by combining the postmortem values of glucose and lactate found in the cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The normal concentration of lactic acid circulating in the blood is about 1 ± 0.5 mmol/L [43]. Coe's findings show that vitreous values reflect serum values at the moment of death, at least in case of normal or high pre-mortem concentrations [44]. It seems that in the initial period after death (probably up to 6 hours) intensive production of lactates occurs in cytosol [29,41,42].…”
Section: Applications Electrolytesmentioning
confidence: 99%
“…VH sodium levels of greater than 155 meq/L have been cited as evidence of dehydration [50]. Although changes occur in post-mortem sodium levels these often remain stable for sufficient time to provide information that may be useful in determining the mechanism of death [26] For example, the ante-mortem serum sodium and chloride concentrations are reflected in post-mortem vitreous values, making it possible to diagnose hyponatremia or hypernatremia at the time of death [1,6,13,14,16,[25][26][27][28]44,49,[51][52][53][54][55][56][57][58][59].…”
Section: Applications Electrolytesmentioning
confidence: 99%
“…Before then, the understanding of these constituents was limited to animals and enucleated human eyes. Subsequently, numerous researchers [4][5][6][7]9,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have performed postmortem biochemical analyses on vitreous humor. These analyses typically focused on levels of vitreous glucose, lactate, sodium, chloride, potassium, urea nitrogen and creatinine.…”
Section: Discussionmentioning
confidence: 99%